CATALYTIC CRACKING OF CORN OIL BY MIXTURE OF H-MCM-41 AND Ni/MCM-41 - , Iip Izul Falah, Sutarno, Didik Arwinsyah ([Yogyakarta] : Chemistry Departement Universitas Gadjah Mada, 2010)
Synthesis of H-MCM-41 and Ni/MCM-41 mesoporous materials as well as activity of their mixture for cracking of corn oil in order to produce biogasoline has been studied. This work was started by synthesis of aluminosilicate MCM-41, which was conducted by mixing sodium silicate and sodium aluminate in ratio of Si/Al=50 using CTAB as a template, where a hydrothermal process was maintained at 100 &#8304